Temperature Effects on the Distribution of Aragonitic and Calcite-Secreting Epifaunal Bivalves - Eichenseer, Kilian; Balthasar, Uwe; Smart, Christopher W; Kießling, Wolfgang (Journal of Biogeography, 2024)
Aim: To test if temperature significantly influences the global biogeographic distribution of marine epifaunal bivalves via their skeletal mineralogy. Location: Global. Taxa: Marine, epifaunal bivalves. Methods: The skeletal mineralogy of 45,789 epifaunal bivalve occurrences from 669 species from the Ocean Biodiversity Information System (OBIS) was related to sea surface temperatures from Bio-ORACLE. Binomial regression was used to assess the influence of temperature and seasonality on the distribution of aragonitic and calcite-secreting bivalve occurrences, aggregated in equal-area grid cells. Results: The proportion of aragonitic bivalve occurrences significantly increases with mean annual temperature in our global analysis and most marine biogeographic realms. A greater prevalence of calcite-secreting bivalves in seasonal climates could be shown at low mean annual temperatures at the global scale but not within biogeographic realms. Main Conclusions: The global biogeographic distribution of epifaunal bivalves is significantly influenced by water temperature via their skeletal mineralogy. The mechanism driving this pattern is best explained by the temperature modulation of the effect of Mg2+ on calcite growth. Although this Mg2+ effect predicts an advantage for aragonite secretion at higher temperatures, poleward migration in response to higher temperature extremes will expose tropical taxa to cooler temperatures in the cold season, which may impede aragonite secretion in taxa not adapted to these climates. Significance: Our results suggest that skeletal mineralogy is likely to influence ocean warming-induced migration patterns.
CRIS-Team Scopus Importer:2024-11-15
Keywords: aragonite; bivalves; calcite; climate change; macroecology; shell mineralogy